Pengaruh Integrated Marketing Communication Terhadap Citra Perusahaan Ortuseight - Muhammad Haidul Fikri; Sa’diyah El Adawiyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Business competition between sports brands is very tight. There is intense competition between brands in Indonesia, for this reason each brand creates a strategy for its brand, such as Integrated Marketing Communication (IMC). In the business world, Integrated Marketing Communication (IMC) is one of the strategies that is the most important point for creating integrated marketing communications in order to attract consumers and build an image. As is done by the local brand, Ortuseight. The theory used is integrated marketing communication which includes advertising, sales promotion, personal selling, public relations, direct and digital marketing, and company image which includes personality, reputation, values/ethics, corporate identity. The approach used in this research is quantitative, using a survey method. Data collection was carried out by distributing questionnaires via Google Form, which were distributed to 60 Instagram followers @sd_3sport, and sampling was carried out randomly. The results of this research show that the influence of Integrated Marketing Communication, all respondents answered agree, and the influence of Integrated Marketing Communication on Company Image, all respondents answered agree. From all the Y variable statements in the research questionnaire, the magnitude of the influence of Integrated Marketing Communication has a strong relationship of 0.864 to the company image of Instagram followers @sd_3sport with a percentage of Integrated Marketing Communication of 74.6% and the remaining 25.4% is influenced by other factors